Medieval Tuscan glasses from Miranduolo, Italy: A multi-disciplinary study - Schiavon, Nicola (2020)
Twenty transparent glass fragments from Miranduolo were analysed by Variable Pressure - Scanning Electron Microscopy - Energy Dispersive System (VP-SEM-EDS), Particle Induced X-Ray Emission and Particle Induced Gamma-Ray Emission (PIXE/PIGE) and Laser Ablation - Inductively Coupled Plasma - Mass Spectrometry (LAICP- MS). The fragments are dated from mid-13th to mid-14th century CE, when the first Tuscan glass-making workshops emerged. Miranduolo did not have an in situ glass-making workshop. Hence, the aim was to determine the glass production technology and raw material provenance. All the glasses are of plant ash (PA) sodalime- silica (Na-Ca-Si) composition, with eighteen being made with Levantine plant ash (LPA), one with Barilla plant ash (BPA), and one Na-Ca-Si glass with high magnesium and low potassium (HMg-LK). The production of LPA glasses can be distinguished according to the use of different sand typologies as former. It seems probable that glasses were produced regionally from multiple Tuscan glass factories.